Utilizing Optimized Tools to Investigate PTM Crosstalk: Identifying Potential PTM Crosstalk of Acetylated Mitochondrial Proteins - Horita, Henrick (Proteomes, 2018)
Post-translational modification (PTM) crosstalk is recognized as a major cell-regulatory mechanism, and studies of several proteins have validated the premise that PTMs work in concert. Previous work by our group investigated the potential PTM crosstalk on proteins in the EGFR-Ras-c-Fos axis by utilizing a comprehensive set of PTM reagents termed Signal-Seeker toolkits. In this study, these tools were used to investigate the potential PTM crosstalk that occurs in acetylated mitochondrial proteins in response to a mitochondrial stress-inducing agent hydrogen peroxide (H(2)O(2)). Mitochondrial protein acetylation has been shown to participate in PTM crosstalk as exemplified by the regulation of the pyruvate dehydrogenase complex via kinase, phosphatase, acetyltransferase, and deacetylase activities. Changes in the acetylated state of mitochondrial proteins were investigated, in response to H(2)O(2), using a novel anti acetyl lysine (Ac-K) antibody. Signal-Seeker PTM detection tools were used to validate the acetylation state of ten mitochondrial targets, as well as their endogenous acetylation state in response to H(2)O(2). Importantly, the endogenous acetylation, ubiquitination, SUMOylation 2/3, and tyrosine phosphorylation state of four target mitochondrial proteins were also investigated with the toolkit. Each of the four proteins had unique PTM profiles, but diverging acetylation and ubiquitin or SUMO 2/3 signals appeared to be a common theme. This proof-of-concept study identifies the Signal-Seeker toolkits as a useful tool to investigate potential PTM crosstalk.